The Relation between Dentofacial Shapes and Depth of Masseter Muscle Using Magnetic Resonance Imaging Technique - Ali Hakiem Tawfieq (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: To determine the depth of masseter muscle in various vertical dentofacial shapes and to relate masseter muscle depth with craniofacial shapes using magnetic resonance imaging technique (MRI). Study design: The participants were split into three teams, each with ten. The chosen participants had lateral cephalograms. Everyone with a history of orthognathic surgery or systemic disorders was not included in the current investigation. Place and duration: Study performed in orthodontic care in different special centres in Baqubah city from October 2021 to June 2022. Methodology: Thirty youthful, healthy people overall between the ages of 16 and 40were chosen and divided into three groups of ten,using(MRI), categorize each as a vertical, average, and horizontal grower. The concepts masseter muscles had their different anatomical dimensions sagittal, axial, and coronal directions utilizing MRI perspectives. Results: Our study found the difference is significant when comparing between the growth patterns in both direction (horizontal and vertical) (p<0.05), also the direction of muscle fibers of masseter muscle (anterior and posterior) away from first molar to the zygomatic arch was saved. In contrast to the horizontal list, when the fibers are attached anteriorly and vertically at the jaw angle, we discovered in our research that the directionof the muscle fibers is toward the posterior side more than anterior side and at a sharper angle. Conclusion: The study show that the muscle fibers located in extra posterior direction and the angle was sharper than the horizontal group, where the vertical fiber orientation having an anterior connection at the angle of the mouth’s. Keywords: MRI, growth patterns, and masseter muscle.